Pengaruh Penerapan Sistem Akuntansi Pemerintah Daerah, Pemahaman Akuntansi, Ketaatan Pada Peraturan Perundangan, dan Motivasi Kerja Terhadap Akuntabilitas Kinerja Instansi Pemerintah Daerah (Studi Empiris Pada Organisasi Perangkat Daerah Kabupaten Kuantan - silvi oktaviani; diskhamarzaweny diskhamarzaweny; yul emri yulis (Program Studi Akuntansi - Universitas Islam Kuantan Singingi, 2019)
The purpose of this research: (1) The effect of Application of Local Government Accounting System To the Accountability Performance of Local Government Kuantan Singingi regency; (2) Understanding of Accounting To the Accountability Performance of Local Government Kuantan Singingi regency; (3) compliance with laws and regulations To the Accountability Performance of Local Government Kuantan Singingi regency; (4) Work Motivation To the Accountability Performance of Local Government Kuantan Singingi regency. This research is descriptive by using quantitave data analysis with causal research design. The data used in this study is the primary data in the form of questionnaires distributed throughout the organization of regional devices Kuantan Singingi Regency. The number of population this research was 161 people and the sample size was 78 people. Data analysis was done by using multiple linear regression method with the help of SPSS version 23 software. In this research uisnh 4 independent variables namely The effect of Application of Local Government Accounting System (X1), Understanding of Accounting (X2), compliance with laws and regulations (X3), Work Motivation (X4), and performance accountability (Y) as its dependent variable. The results of this study indicatethat the Application of Local Government Accounting System has a positive and significant impact on the Accountability Performance of Local Government Kuantan Singingi regency of 0.281. Understanding of Accounting has a positive and significant impact on the Accountability Performance of Local Government Kuantan Singingi regency of 0.217. Unlike the utilization of compliance with laws and regulations has no significant impact on the Accountability Performance of Local Government Kuantan Singingi regency of 0.092. But Work Motivation has a positive and significant impact on the Accountability Performance of Local Government Kuantan Singingi regency of 0.166.